Effect of axial preload on durability of aerospace fastened joints. (March 2018) - Benhaddou, Taha; Stephan, Pierre; Daidie, Alain; Alkatan, Feras; Chirol, Clement; Tuery, Jean-Baptiste
Highlights: Effect of axial preload on double lap fastened joints' durability is studied. Innovative iterative tightening technique is used to achieve an accurate preload level. High preload has a negligible effect on static life and a beneficial effect on fatigue life. Numerical model explains experimental findings through analysis of fatigue-linked parameters. Fatigue life analysis shows that Crossland criterion is suitable for predicting double lap fastened joints' durability. Abstract: The main aim of the present work is to study the effect of axial preload on the durability of aerospace fastened joints. For that purpose, experimental and numerical approaches are adopted to demonstrate the beneficial effect of axial preload on the fatigue life of representative aerospace fastened joints. In the experimental approach, an innovative tightening technique, based on iterative tightening, is used to reduce the scatter habitually induced on preload when the conventional torque tightening technique is employed. The main benefit, besides the use of this alternative tightening technique, is to allow an accurate preload to be introduced without geometry or stiffness modification, thus enabling the preload effect to be determined precisely. The results show the effect of preload on the static resistance, fatigue life and failure mode of fastened joints. In the numerical approach, a 3D finite element model is developed and the analysis of its behavior confirms and explains experimental observations. Analysis of longitudinal stresses through critical paths shows that the effect of high preload is beneficial because it reduces hydrostatic pressure and shear stress amplitude, thus leading to longer fatigue lives. The correlation between experimental observations and the numerical results is studied using SWT and Crossland multiaxial fatigue criteria. Graphical abstract: